MANAJEMEN PENGENDALIAN TRANSAKSI PENGELUARAN PADA KPP MALANG SELATAN - Wulandari, Siska Devi; Situmorang, Dokman Marulitua (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Cash disbursements are transactions that result in a reduction in cash balances in the State Revenue and Expenditure Budget either in cash through Stock Money or from state cash accounts originating from expenditures, purchases of capital goods, transfer expenditures via government credit cards or other expenditures . Internal control is a process implemented or influenced by stakeholders designed to provide adequate assurance regarding the achievement of organizational goals. Therefore, it is necessary to know the controls that have been carried out in cash disbursement transactions so that we can determine whether cash disbursement transactions have been carried out properly so as to achieve organizational goals. It is hoped that this article will provide knowledge about Government Accounting, especially cash disbursement transactions.